Da totalidade à força do lugar: o pensamento de Milton Santos, à luz da Semiótica de Peirce - Vieira, Patricia Laundry Mollo (2019)
The theme of this thesis is the analysis of the thought of the geographer Milton Santos (1926-2001), from the semiotics of the North American Charles Sanders Peirce (1839-1914). We propose, in this work, to apply the prototype of genuine semiosis, developed from Parmentier (1948-), to accompany the expansion of Milton Santos's thinking about a set of selected works, beginning in the 70's. We defend the hypothesis of which the method present in the work The nature of space. Technique, time, reason and emotion (1996) made possible the internalization of the categories of analysis present in The work of the geographer in the third world (1978) and For a new geography (1978) in triadic relational patterns that allowed him to assume space under a general system of rules in order to predict the future course of his conduct. We suppose that, in addition to suggesting the prototype of semiosis as a method for analysis of geographic thought, the thesis contributes to highlight the logic of Milton Santos' thinking in the search for operationality and coherence of the method, which marked a trajectory of research linked to the permanent attention to the present and the desire to offer a geography capable of restoring to man the solidarily inhabited space